Political consequences of (consumer) debt relief - Toke Aidt; Zareh Asatryan; Lusine Badalyan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Many governments operate consumer debt relief programs, often timed to match the election cycle, but their political effects are not well understood. We ask if debt relief can influence elections in democracies. Our motivating exercise is the Biden administration's promise to relieve student debt. We utilize quasi-experimental variation generated by another very large debt relief program enacted in the Republic of Georgia that, similar to USA, affected every sixth voter. We estimate that the program helped the incumbent candidate win that election, and that its effects persisted. Overall, we show how economic power can translate into political power in democracies.
Keywords: G51; D72; 330; Consumer debt relief; US student debt; distributive politics; vote buying; elections